Preparation of a Novel Heterocycle-Containing Polystyrene Chelating Resin and its Application for Hg(II) Adsorption in Aqueous Solutions - Xiong, Chunhua; Chen, Xinyi; Yao, Caiping (Current Organic Chemistry, 2012)
A novel chelating resin with a facile and efficient methodology was synthesized from chloromethylated polystyrene beads (PSCl). The resulting polymer functionalized with 3-amino-5-methylisoxazole (AMI) has been characterized by elemental analysis and infrared spectra. The effects of reaction parameters of AMIR chelating resin (reaction solvent, reaction temperature and molar ratio of reagents) were monitored to specify the best synthesis conditions. The functional group capacity and percentage conversion of functional group of AMIR prepared under the optimum condition were 2.39 mmol/g and 52.0%, respectively. The resin was employed for selective separation and preconcentration of Hg(II) ions in aqueous solutions since it showed higher affinity towards Hg(II) compared to Cd(II), Pb(II), Cu(II), Zn(II) or Ni(II). Effects of experimental conditions including pH, temperature and initial metal ion concentration for separation and preconcent ration of Hg(II) were investigated. The maximum adsorption capacity of AMIR for Hg(II) is 335.6 mg/g at 298 K, calculated from the Langmuir model. Desorption studies revealed that Hg(II) ions could be eluted effectively by using the 2.0 mol/L HNO3 solution without any adsorption capacity decrease of the AMI resin. The resin has a potential use for separation and prconcentration of Hg(II) ions from contaminated natural waters.
Keywords: 3-amino-5-methylisoxazole